Nexus between Light Pollution and Air Temperature: A Study of Bangladesh - Howlader, Aninda Sundar; Islam, Kazi Saiful (Journal of Bangladesh Institute of Planners, 2018)
Rapid urbanization and population growth have introduced a new phenomenon called “light pollution”, which is the result of ungoverned use of artificial lighting. Natural land cover is being replaced by impervious surface to meet the growing demand. As a result, urban areas are getting warmer compared to the surrounding rural areas. Scholarly literature confirms the relationship between light pollution and air temperature. However, the nature of direct relationship is yet to be explored. Using remote sensing and weather station data, this research reveals the nature of relationship between these two variables. The analysis confirms that a significant relationship exists which can be explained by geographically weighted regression (GWR) in a far better way compared to ordinary least square (OLS) regression. According to the GWR, overall 50% change in air temperature is influenced or affected by light pollution, where in urban areas the impact of light pollution on air temperature is higher compared to rural areas. This research also unearths that light pollution is increasing at a dissolute rate, four-fold in 10 years. With this said, considering the nexus between light pollution and air temperature along with its other negative effects the authorities are expected to take measures to reduce light pollution. JBIP, Vol. 11, 2018 (Printed in June 2020), pp. 1-9